ANOMALI PASAR PADA RETURN SAHAM LQ 45 DI BURSA EFEK INDONESIA: FENOMENA THE DAY OF WEEK EFFECT, WEEK FOUR EFFECT, ROGALSKY EFFECT, DAN JANUARY EFFECT - Reza Widhar Pahlevi (Fakultas Bisnis UKDW, 2016)
Market anomalies appears on all forms of efficient markets, both weak form, semi-strong and strongform. But plenty of evidence to link the anomaly with semi-strong form efficient market exploited togenerate abnormal returns. Market anomalies that is often discussed is the Day of the Week Effect,January Effect, Week Four Effect and other market anomalies. Empirical research is intended todetermine whether there is the phenomenon of the day of the week effect, week four effect, the effectrogalsky and January effect on LQ 45 stocks in the Indonesia Stock Exchange year period 2014-2015.Based on the analysis of data, shows that there is the phenomenon of the day of week effect on thecompany LQ-45 in Indonesia Stock Exchange 2014-2015 period, there is the phenomenon of weekfour effect on the LQ-45 in Indonesia Stock Exchange 2014-2015 period, there are phenomenonRogalski Effect on the LQ-45 in Indonesia Stock Exchange 2014-2015 period and there is no Januaryeffect phenomenon in the LQ-45 in Indonesia Stock Exchange 2014-2015 period.Keywords: the day of the week effect, week four effect, rogalsky effect and january effect